Preparation of biologically active Arabidopsis ribosomes and comparison with yeast ribosomes for binding to a tRNA-mimic that enhances translation of plant plus-strand RNA viruses - Stupina, Vera A.; Simon, Anne E. (Frontiers in Plant Science, 2013)
Isolation of biologically active cell components from multicellular eukaryotic organisms often poses difficult challenges such as low yields and inability to retain the integrity and functionality of the purified compound. We previously identified a cap-independent translation enhancer (3’CITE) in the 3’UTR of Turnip crinkle virus (TCV) that structurally mimics a tRNA and binds to yeast 80S ribosomes and 60S subunits in the P-site. Yeast ribosomes were used for these studies due to the lack of methods for isolation of plant ribosomes with high yields and integrity. To carry out studies with more natural components, a simple and efficient procedure has been developed for the isolation of large quantities of high quality ribosomes and ribosomal subunits from Arabidopsis thaliana protoplasts prepared from seed-derived callus tissue. Attempts to isolate high quality ribosomes from wheat germ, bean sprouts and evacuolated protoplasts were unsuccessful. Addition of purified Arabidopsis 80S plant ribosomes to ribosome-depleted wheat germ lysates resulted in a greater than 1200-fold enhancement in in vitro translation of a luciferase reporter construct. The TCV 3’CITE bound to ribosomes with a 3 to 7-fold higher efficiency when using plant 80S ribosomes compared with yeast ribosomes, indicating that this viral translational enhancer is adapted to interact more efficiently with host plant ribosomes.